Pengoperasian Waduk dalam Rangka Penanganan Bahaya Kekeringan dan Banjir - Suharyanto, Suharyanto (Department of Civil Engineering, Diponegoro University, 2005)
This paper present the use of stored water in reservoir more optimally by developing operation policy which is able to anticipate the dry and wet (flood) conditions. The reservoir operationÂ policy which is able to anticipate those conditions will result in more efficient use of water throughout the whole year season, i.e., minimising spillage during wet (flood) season and yet conserving water during dry season. When the dry season is incoming, the operation policy will direct to release less water than during the normal condition, thus conserving water. When the wet (flood) season is coming, the operation policy will direct to release more water to give attenuation volume in the reservoir such that during the rainstorm it can store the excess weter. The operation policy which has capability to anticipate the incoming condition is developed by employing Stochastic Dynamic Progamming (SDP) imbedded with fuzzy infrencing technique. The performance of the generated operating policy from SDP is evaluated by simulating the reservoir operation inplementing the generated operation policy under three conditions, i.e., normal, dry and wet (flood) conditions. It shows that the use of fuzzy inferencing embedded within the SDP program and in the simulation program can result in more flexible operation policy.Keywords: Pengoperasian Waduk, Optimasi, Fuzzy InferencingPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3897[How to cite: Suharyanto, 2005, Pengoperasian Waduk dalam Rangka Penanganan Bahaya Kekeringan dan Banjir, Jurnal Media Komunikasi Teknik Sipil, Volume 13, Nomor 1, pp. 60-70]